The emergence of different names assigned to Behavioral Therapy in Brazil (Brazilian Journal of Behavioral and Cognitive Therapy, 2011)
In the last decade in the Behavioral Analysis community in Brazil happened the emergence of different therapeutic interventions with different denominations: Analytic-Behavioral Therapy, Contingencies of Reinforcement Therapy, Molar and Self-Knowledge Therapy and Pragmatic Behavioral Psychotherapy. It is observed that despite the differences, the similarities found in the above therapies raise doubts about the necessity of creating new denominations to this clinical practice. Eventually, all the models are based on Behavior Analysis and use the contingency analysis as a tool of analysis and intervention aiming to understand the individual as a whole. The Brazilians therapists’ concern about their practice can be seen as productive and desirable. However, rethinking in a critical way, going deeply into the theoretical conceptions and enlarging the behavior analysis do not mean that new models and concepts are being created. If they are accepted as “new intervention models”, this can result in the dismemberment and weakening not only of this approach but also the risk of fragmented application use of the knowledge corpus and scientific methods which are the foundation of the behavioral therapist’s interventions.
Keywords: Analytic-Behavioral Therapy; Contingencies of Reinforcement Therapy; Molar and Self-Know-ledge Therapy and Pragmatic Behavioral Psychotherapy